Qualidade fitossanitária: proposição de um modelo para gestão de prevenção do cancro cítrico na produção de laranjas no estado de São Paulo. - Sala, Simon Podolsky (2003)
Citrus canker is one of the main threats to the sanity of orange groves in the production region of the State of Sao Paulo, known as Citrus Belt. This disease has caused the elimination of million of trees and losses to the whole citrus production chain. Despite the official measures to canker eradication, growers can prevent having the disease in their groves adopting simple measures, recommended by FUNDECITRUS Fund for Citriculture Defense. These measures could be standardized and implemented in the citrus farms using approaches and tools for quality management by means of a management system upon which a phytossanitary quality certificate for citrus canker prevention can be established. This certificate could contribute do the to the reduction of the risks of occurrence and to the reduction of costs for the canker prevention and eradication. Besides that, the phytossanitary quality certificate could originate the establishment of a quality and origin certificate for the orange produced in the Citrus Belt, aiming the valuation of the state citriculture in internal and foreign orange markets, following the recent trends of quality certification of agro-food products and companies. The model for citrus canker prevention management system is proposed from a survey of quality certification systems in agrofood chains and the ISO 9000:2000 standards, SQF 2000 code and IFP Integrated Fruit Production system guidelines. A survey with 64 growers has been conducted to evaluate the adoption of prevention measures recommended by FUNDECITRUS and the growers´ perception of the prevention measures and of an eventual phytossanitary quality certificate for citrus canker prevention.